Limits and strategies of health professionals on adherence to treatment of diabetes: integrative review - Majoi Dias Prado; Daniela Arruda Soares (Revista de Pesquisa Cuidado é Fundamental Online)
This paper aimed to know the limits and strategies of health professionals in the process of joining the treatment of those with diabetes throughout an integrative review. It was analyzed a period of ten years. Six pre-established stages were followed in order to select and analyze data. 388 articles were found, however only 15 fitted the inclusion criteria. When it comes to the health professionals' limits in face of the diabetes accession process, three thematic cores arose: organizational factors, professional factors and individual factors. The strategies used by these professionals in order to enlighten the accession were grouped in individual proposals, interprofessionals and relationship with the client. The professionals seem to understand how wide the limits of their practice are and do not save effort for a better outcome. It was clear how important understanding the issues related to the accession process is, as well as the lack of studies focused on such aspects under a professional perspective.